Testing for Twin Deficits and Ricardian Equivalence Hypotheses: Evidence from Iran - Bagheri, Farzane; ., Salma Keshtkaran (Journal of Social and Development Sciences, 2012)
The main purpose of this study is to examine the relationship between budget deficit and current account deficit in Iran from 1971 to 2007. Twin deficits, which argues that a larger budget deficit leads to an expanded current account deficit, and Ricardian equivalence hypothesis, which states that there is no casual relationship between these two deficits, are examined for this purpose. To achieve this goal, Johansen co-integration and Granger causality tests are used for the period under study. The results indicate that there exists a long run equilibrium link between budget deficit and current account deficit. There is a one-way causality relationship from the budget deficit toward the current account deficit.